Studies on the production of synthetic seeds of Bacopa monnieri (L.) Wettst. - Ranjan, Ritika (My University, 2015)
Bacopa monnieri (L.) Wettst., (family Scrophulariaceae) is a traditional Indian Ayurvedic plant with high commercial value is used for the treatment of neurological disorders. The present study was focused to study the factors affecting production of artificial seed for mass propagation and storage of B.monnieri using apical shoot and somatic embryo as explants. The morphology and germination ability of encapsulated explants was influenced by the concentration of sodium alginate and calcium chloride (CaCl₂.2H2O) and also percolation time. Sodium alginate (3% w/v) and 125 mM calcium chloride were found to be optimum for synthetic seeds formation. The beads, which were formed using 3% (w/v) sodium alginate in combination with 125 mM calcium chloride were of smooth, transparent, uniform size and isodiametric. Role of percolation (complexing) time in synthetic seed formation was also evaluated. Sodium alginate encapsulated explants, complexed for 15 min in presence of calcium chloride resulted in highest germination (100.00%). Encapsulated shoot tips and somatic embryos were stored at 4˚C (cold temperature) and 25˚C (room temperature). Encapsulated somatic embryos were able to generate even after storage of 140 days at both temperature, whereas encapsulated apical shoots were not able to germinate after 20 days when stored at 4˚C. During storage somatic embryos showed high conversion percentage at all time intervals as compared to shoot buds. The encapsulated shoot tips stored at 4˚C showed maximum percent germination 91.66% and 100 % at 25˚C and lowest germination frequency was 0 % at 4˚C and 25% at 25˚C. The amplified PCR based Random Amplified Polymorphic DNA (RAPD) and Inter Simple Sequence Repeat (ISSR) markers showed all monomorphic bands in regenerated plants after storage and also mother plant, indicates clonal uniformity.
MT, DBT
Keywords: Bacopa monnieri, synthetic seeds, Random Amplified Polymorphic DNA, Inter Simple Sequence Repeat, storage of germplasm, conservation.; DBT